The Evolution of Bluetooth: A Deep Dive - Subhagato Dutta (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The evolution of Bluetooth technology represents a significant milestone in wireless communication, transforming from its initial incarnation as a basic short-range protocol to a sophisticated communication standard supporting diverse applications. This comprehensive article traces Bluetooth’s development through multiple generations, examining the technological advancements that have shaped its capabilities. It explores the progression from basic frequency-hopping spread spectrum implementation to advanced features including Enhanced Data Rate, Adaptive Frequency Hopping, and Low Energy protocols. Key developments in mesh networking, power efficiency, and connection management are analyzed, along with their impact on device interoperability and network performance. The article also investigates Bluetooth’s position within the broader wireless technology landscape, including its relationship with complementary and competing standards such as Ultra-Wideband and NFC. Through a detailed examination of implementation challenges, performance metrics, and technological innovations, this article provides insight into Bluetooth’s evolution from simple point-to-point connections to its current role as a cornerstone of modern wireless communication, particularly in IoT applications and complex network environments.